Use of Internet Platforms for Information About Sensitive Teeth Among Indonesian Adults: A Cross-Sectional Study - Khairina, Safira; Maharani, Diah Ayu; Yavuz, Yasemin; Setiawati, Febriana (Makara Journal of Health Research, 2021)
Background: The behavior of seeking oral health information (OHI), especially the topic of sensitive teeth (ST), among the Indonesian adult population has rarely been studied. Hence, the current work aimed to analyze the characteristics of the Indonesian adult population who reported having ST and to explore their practice of self-medication in terms of their behavior of seeking OHI on the internet. Methods: A cross-sectional study was conducted between January and March 2021 in Indonesia. This study used a self-administered questionnaire comprising questions about sociodemographic data, oral health behavior, diet, and subjective oral health. Bivariate analysis based on a chi-square test was conducted for statistical evaluation. Results: Results showed that 63.3% of the respondents used Google, 24.5% used Instagram, and 24.2% used YouTube to search for OHI about ST. Most of them felt improvement with self-perceived medication, with YouTube (odds ratio [OR] = 5.13, 95% confidence interval [CI] = 2.26, 11.62), Google (OR = 2.94, 95% CI = 1.79–4.84), and Instagram (OR = 1.84, 95% CI = 1.11, 3.06) as their main OHI sources. Conclusions: Internet platforms provide information that helps adults to cope with their ST. Professionals should consider using internet-based interventions as a powerful tool for dental health education.